Strategi Efektif Pembelajaran Berdiferensiasi untuk Meningkatkan Hasil Belajar Siswa - St. Shofiyah; Kamila, Nur; Nur Safitri, Muharofah; Kusumawati, Dahani (Kependidikan Islam Fakultas Agama Islam, 2024)
Differentiated learning has begun to be implemented in several schools in Indonesia, one of which is SMA Negeri 1 Panji Situbondo. This research aims to describe implementation steps and improving learning outcomes through differentiated learning in class XI-9 in the subjects of Islamic Religious Education (PAI) and Characteristics.. This research was conducted in less than one month with the research location at SMA Negeri 1 Situbondo banner.Data collection methods in this research include observation, interviews, and documentation studies. After the data was collected, analysis was carried out using a qualitative approach with a phenomenological type of research. The research results show that differentiated learning has been implemented systematically. The process begins with mapping student learning needs, obtained through an initial assessment in the form of a pretest. Next, the teacher develops learning modules that are adapted to the mapping results using four main approaches: differentiation of content, process, product and learning environment. The implementation of differentiated learning is carried out in accordance with the planning and schedule set by the school. The final step is reflection and evaluation using formative and summative assessments to measure improvements in student learning outcomes. The research results showed that after implementing differentiated learning, student learning outcomes in class XI-9 experienced a significant increase. It is hoped that this research can become a reference for educators and policy makers in improving teaching strategies that are more adaptive and effective, so as to maximize students' learning potential optimally.